Strengthening Spiritual Character and Empathy through School Religious Activities - Hikmayana, Dian (Agrapana Media, 2025)
This study aims to analyze the role of school religious activities in strengthening students’ spiritual character and empathy at MTs Islahiyah Kalitidu. The background of this research stems from the phenomenon of weakening spiritual character and low social empathy among students, which requires an educational approach based on religious values. The research method used is a qualitative approach with a descriptive study design. Data were collected through observation, in-depth interviews with teachers and students, as well as documentation of school religious activities such as congregational prayers, Qur’an recitation (tadarus), regular Islamic studies, and religious social activities. The results show that religious activities play an important role in instilling spiritual values such as faith, honesty, patience, and sincerity, while also fostering social empathy through practices of sharing, caring, and helping among students. Teachers and mentors contribute significantly as role models in developing these characters through humanistic and contextual approaches. Moreover, the religious and participatory school environment serves as a key supporting factor in the successful internalization of character values.